2013
DOI: 10.1002/cmdc.201300216
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Rose Bengal Analogues as SecA Inhibitors

Abstract: SecA, a key component of bacterial Sec-dependent secretion pathway, is an attractive target for exploring novel antimicrobials. Rose bengal (RB), a polyhalogenated fluorescein derivative, was found from our previous study as a potent SecA inhibitor. Here we describe the synthesis and structure-activity relationships (SAR) of 23 RB analogues that were designed by systematical dissection of RB. Evaluation of these analogues allowed us to establish an initial SAR in SecA inhibition. The antimicrobial effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 57 publications
(138 reference statements)
1
54
0
Order By: Relevance
“…These limitations may explain why, as far as we know, no bacterial channel has previously been expressed in the oocytes; the proteo-liposome injection may allow future studies of other bacterial channels. Moreover, the semi-physiological assays of channel activity in the oocytes allow the assessments of functional activities of SecA homologs from other bacteria and inhibitors [25,29] that otherwise are not available. Another advantage of proteoliposome injection is the ability to reconstitute with interacting membrane complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations may explain why, as far as we know, no bacterial channel has previously been expressed in the oocytes; the proteo-liposome injection may allow future studies of other bacterial channels. Moreover, the semi-physiological assays of channel activity in the oocytes allow the assessments of functional activities of SecA homologs from other bacteria and inhibitors [25,29] that otherwise are not available. Another advantage of proteoliposome injection is the ability to reconstitute with interacting membrane complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The SecA-mediated channel activity in oocytes requires the presence of functional SecA and precursors, as well as bacterial membranes [4]. The channel activity is inhibited by the ATP analog AMP-PCP and by the SecA inhibitors azide and Rose Bengal [4,25]. However, channels composed of SecA-liposomes alone are less efficient, requiring larger amounts of SecA and ATP-Mg 2+ for activity, and losing signal peptide specificity [23].…”
Section: Introductionmentioning
confidence: 98%
“…More recently RB analogs were developed as potent SecA inhibitors. 33 A recent review summarizes all SecA inhibitors reported in the literature. 34 We have continued our structural optimization efforts on the benzothiazole derivatives to afford different classes of pyrimidine (thiouracil) analogs and Figure 1 summarizes major inhibitors obtained in going from virtual screening hit to the latest inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we screened a series of compounds including fluorescein analogs using a truncated form of SecA EcN68 which has higher intrinsic activity and is more sensitive to inhibitors [21,24,25,26]. We have found Rose Bengal (RB) to be an effective SecA inhibitor at sub-micromolar for SecA-mediated translocation ATPase and protein translocation [21].…”
Section: Resultsmentioning
confidence: 99%
“…However, azide does not affect SecA intrinsic ATPase activity [20]. Other SecA inhibitors have been reported [24,25,26]. Rose Bengal (RB) is the first reported sub-micromolar inhibitor in ATPase activities and protein translocation [21].…”
Section: Introductionmentioning
confidence: 99%